Tyrosine-Based Signals Regulate the Assembly of Daple⋅PARD3 Complex at Cell-Cell Junctions - Ear, Jason; Saklecha, Anokhi; Rajapakse, Navin; Choi, Julie; Ghassemian, Majid; Kufareva, Irina; Ghosh, Pradipta (iScience, 2020)
Polarized distribution of organelles and molecules inside a cell is vital for a range of cellular processes and its loss is frequently encountered in disease. Polarization during planar cell migration is a special condition in which cellular orientation is triggered by cell-cell contact. We demonstrate that the protein Daple (CCDC88C) is a component of cell junctions in epithelial cells which serves like a cellular “compass” for establishing and maintaining contact-triggered planar polarity. Furthermore, these processes may be mediated through interaction with the polarity regulator PARD3. This interaction, mediated by Daple's PDZ-binding motif (PBM) and the third PDZ domain of PARD3, is fine-tuned by tyrosine phosphorylation on Daple's PBM by receptor and non-receptor tyrosine kinases, such as Src. Hypophosphorylation strengthens the interaction, whereas hyperphosphorylation disrupts it, thereby revealing an unexpected role of Daple as a platform for signal integration and gradient sensing for tyrosine-based signals within the planar cell polarity pathway. [Display omitted] •Daple localizes to cell junction, regulates planar cell migration•Localization requires Daple's C-terminal PDZ-binding motif (PBM)•The PBM binds a PDZ module of the polarity determinant PARD3•The Daple⋅PARD3 interaction is regulated by tyrosine-based signals Biological Sciences; Cell Biology; Functional Aspects of Cell Biology